Konsep Teologi Hasan Hanafi - Syarifuddin Syarifuddin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
Hasan Hanafi is a modernist scholar whose ideas focus on renewing and reconstructing Islam. These ideas can be witnessed through his great concept on al-Turats wa al-Tajdid (Tradition and renewal) and Al-Yasar al Islam (left Islam), both were publicized in 1981. These concepts are interpretation and renewed form of Jamaluddin‟s and Muhmmad Abduh‟s al Urwatul Wutsq. Hasan Hanafi argues that theology as a science acts as deed analytical tool, while social knowledge is applications of faith system. In his analysis, tradition is not fixed form of deed and past institutions. It is representing the concept of prescriptive norms from developing faith traditions, which constantly under construction process. Hasan Hanafi‟s theological concept is in line with ideas of humanities, union, populism, justice, and social stability. As if, in his hand theology is understood as a protest, social critic, and revolution that focus on human understanding on the historical reality of humanity, which has been proceeded for centuries.